The role of IgG4 (+) plasma cells in the association of Hashimoto's thyroiditis with papillary carcinoma. Issue 12 (6th August 2014) - Taşli, Funda; Özkök, Güliz; Argon, Asuman; Ersöz, Didem; Yağci, Ayşe; Uslu, Adam; Erkan, Nazif; Salman, Tarik; Vardar, Enver
<x xml:space="preserve">Abstract</x> Hashimoto's thyroiditis (HT) is considered to be a risk factor for the formation of papillary carcinoma. The association of IgG4‐related sclerosing disease with tumor is reported to be as sporadic cases in many organs. In this study, it was intended to re‐classify the HT diagnosed cases on the basis of the existence of IgG4 (+) plasma cells; to investigate the clinicopathologic and histopathologic features of the both groups; and in addition, to evaluate the papillary carcinoma prevalence in IgG4 (+) and IgG4 (−) HT cases as well as the prognostic parameters between these groups. Totally 59 cases between the years 2008–2013, 29 of which contain Hashimoto thyroiditis diagnosis in total thyroidectomy materials, and 30 of which contain the diagnosis of HT+papillary carcinoma, were included in the study. The materials were immunohistochemically applied IgG and IgG4; and the cases were classified in two groups as IgG4‐positive HT and IgG4‐negative HT containing cases, on the basis of IgG4/IgG rate. All histopathologic and clinicopathologic parameters between these two groups, as well as their association with papillary carcinoma were investigated. Thirty eight (64.4%) of total 59 cases were NonIgG4 thyroiditis, and 21 (35.5%) were IgG4 thyroiditis. Tumors were detected in 14 (36.8%) of the NonIgG4 thyroiditis cases, and in 16 (76.1%) of the IgG4 thyroiditis cases. The association of IgG4 thyroiditis with tumor is statistically significant (p < 0.004). Multifocality was found to be at a higher rate in IgG4 thyroiditis cases. Perithyroidal extension was detected in six of the cases with tumor, and five of the six cases were IgG4 thyroiditis cases. The association of IgG4 (+) HT cases with increased papillary carcinoma prevalence is suggestive of that IgG4 (+) plasma cells can play a role in carcinogenesis in papillary carcinomas developed in HTs, without a chronic sclerosing ground. In addition, although the number of cases is limited, the high‐association of IgG4 (+) plasma cells with adverse prognostic parameters such as multifocality and extrathyroidal extension is attention‐grabbing. To render these possibilities evaluable, studies to be carried out with larger case series are needed.